No risk, no fun…ctioning? Perceived climate risks, but not nature connectedness or self-efficacy predict climate anxiety - Reese, Gerhard; Rueff, Maria; Wullenkord, Marlis C. (Frontiers in Climate, 2023)
The consequences of climate change are becoming increasingly visible. Recent research suggests that people may respond to climate change and its predicted consequences with a specific anxiety. Yet, little is known about potential antecedents of climate anxiety. The current study aimed to understand the contribution of climate risk perception to climate anxiety, along with nature-connectedness, self-efficacy, and political orientation. With a sample of 204 German adults, we assessed these constructs together with environmental policy support that may result from climate anxiety. Stronger risk perception and a left political orientation predicted climate anxiety. Self-efficacy and nature connectedness, however, were unrelated to climate anxiety. In line with previous studies, climate anxiety correlated positively with environmental policy support but did not predict environmental policy support when controlling for climate risk perception. We discuss results with regard to further developing the concept of climate anxiety and its dynamics and suggest directions for future research.